Job Selection Criteria of Accounting Ph.D. Students and Faculty Members. - Kida, Thomas E.; Mannino, Ronald C. (The Accounting Review, 1980)
Abstract ABSTRACT: This study measures and examines variables that accounting doctoral students and accounting faculty members use in selecting a teaching position. Differences in perceptions of variable importance between doctoral students and faculty are analyzed using factor analysis and a ranking procedure. While the analysis indicated that some similarities exist in the perceived importance attached to many criteria by the students and faculty, it also detected a number of significant differences.